2022
DOI: 10.1002/clc.23877
|View full text |Cite
|
Sign up to set email alerts
|

Dose‐dependent effect of impaired renal function on all‐cause mortality in patients following percutaneous coronary intervention

Abstract: Objective To determine the risk prediction of various degrees of impaired renal function on all‐cause mortality in patients following percutaneous coronary intervention (PCI). Background Patients with chronic kidney disease (CKD) are at high risk of all‐cause mortality after PCI. However, there are less data of various degrees of impaired renal function to predict those risks. Methods This was a subgroup analysis of nationwide PCI registry of 22 045 patients. Patients were classified into six CKD stages accord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
(83 reference statements)
0
5
0
Order By: Relevance
“…Cardiovascular disease is the main reason for illness and death in this group of patients, and CAD plays a significant role [1,27]. Given distinctive changes in lipid and glucose metabolism, it may not be appropriate to extrapolate findings from CAD patients with normal kidney function to patients with ESRD and CAD [3,4,[17][18][19][20][21]. Assessing the importance of the TyG index in risk stratification in this group of patients is of great therapeutic significance, considering the increasing number of individuals with ESRD and CAD, as well as the potential prognostic significance of the TyG index.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cardiovascular disease is the main reason for illness and death in this group of patients, and CAD plays a significant role [1,27]. Given distinctive changes in lipid and glucose metabolism, it may not be appropriate to extrapolate findings from CAD patients with normal kidney function to patients with ESRD and CAD [3,4,[17][18][19][20][21]. Assessing the importance of the TyG index in risk stratification in this group of patients is of great therapeutic significance, considering the increasing number of individuals with ESRD and CAD, as well as the potential prognostic significance of the TyG index.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiovascular events are significantly more likely to occur in patients with end-stage renal disease (ESRD), who are considered a highly susceptible subset of coronary artery disease (CAD) [ 1 , 2 ]. The risk of one-year major adverse cardiovascular events (MACE) for these patients is more than five times greater than that of patients without ESRD [ 3 , 4 ]. Notably, the excess risk in patients with ESRD and CAD cannot be solely attributed to traditional cardiovascular risk factors [ 1 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…As the main results of our study, the history of ACKD remains independently associated with in-hospital death following PCI even after adjusting baseline parameters such as other cardiovascular risk profiles. In many studies, chronic renal failure, especially frequent dialysis, has been declared as a potential risk factor for adverse outcomes of therapeutic interventions in patients with coronary heart disease, especially following revascularization (13)(14)(15)(16)(17). This higher mortality can be explained by the use of contrast material, disorders related to circulating blood volume, thromboembolic disorders related to kidney disease, and significant hemodynamic disorders in the mentioned patients (18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
“…In several trials, the presence of underlying chronic kidney disease was considered a major risk factor for long-term poorer outcomes following PCI, such as higher mortality and progression of renal impairment (8)(9), also the impaired renal elimination of antithrombotic drugs exposes these patients to a higher likelihood of bleeding complications (10)(11). During our literature review on databases, we found a small number of studies looking into the impacts of PCI on ACKD patients, Limpijankit and his colleague as one of the few studies in this matter determined one-year survival of PCI among 207 CKD patients stage 4-5 without dialysis and 5 with dialysis was 65.2%, 68.0% and 69.4 respectively (12). Therefore, the outcome of PCI procedures in patients with ACKD still remains uncertain.…”
mentioning
confidence: 97%
“…Patients with CAD and chronic kidney disease (CKD) face a higher risk of bleeding and ischemic events, which significantly impacts clinical prognosis ( 9 ). Thus, antiplatelet treatment for these patients requires extra caution to balance the risks of bleeding and ischemia.…”
Section: Introductionmentioning
confidence: 99%